Is there any Influence of Variations in Context on Object-Affordance Effects in Schizophrenia? Perception of Property and Goals of Action - Sevos, Jessica; Grosselin, Anne; Brouillet, Denis; Pellet, Jacques; Massoubre, Catherine (Frontiers in Psychology, 2016)
The simple perception of an object can potentiate an associated action. This affordance effect depends heavily on the action context in which the object is presented. In recent years, psychologists, psychiatrists and phenomenologists have agreed that subjects with schizophrenia may not perceive the affordances of people or objects that could lead to a loss of ease in their actions. We examined whether the addition of contextually congruent elements, during the perception of everyday objects, could promote the emergence of object-affordance effects in subjects with schizophrenia and controls. Participants performed 2 Stimulus-Response-Compatibility tasks in which they were presented with semantic primes related to sense of property (Experiment 1) or goal of action (Experiment 2) prior to viewing each graspable object. Controls responded faster when their response hand and the graspable part of the object were compatibly oriented, but only when the context was congruent with the individual’s needs and goals. When the context operated as a constraint, the affordance-effect was disrupted. These results support the understanding that object-affordance is flexible and not just intrinsic to an object. However, the absence of this object-affordance effect in subjects with schizophrenia suggests the possible impairment of their ability to experience the internal simulation of motor action potentialities. In such case, all activities of daily life would require the involvement of higher cognitive processes rather than lower level sensorimotor processes. The study of schizophrenia requires the consideration of concepts and methods that arise from the theories of embodied and situated cognition.